The Influence of Servqual on Customer Satisfaction and Customer Loyalty in After Sales Service at PT XYZ Kalimalang Branch - Lando, Rolan Adhytia; Sitorus, Marison; Maulana, Rizky; Jatmiko N, Yulius (CV. Ulil Albab Corp, 2024)
This journal contains research aimed at analyzing the influence of SERVQUAL on Customer Satisfaction and Customer Loyalty at PT XYZ Kalimalang Branch. Using SmartPLS 3.29 statistical processing software and the Structural Equation Modeling-Partial Least Square (SEM-PLS) method to seek answers. The sample used in the analysis in this study consists of 110 post-sales customers of PT XYZ over a certain period selected using Purposive Sampling method. Based on quantitative data from questionnaires filled out by visitors, the results indicate that SERVQUAL influences Customer Satisfaction and customer loyalty (Through Customer Satisfaction Mediator). Furthermore, based on the calculation results, it was also found that SERVQUAL does not significantly influence Customer Loyalty directly.